Genomics and cellulolytic, hemicellulolytic, and amylolytic potential of Iocasia fonsfrigidae strain SP3-1 for polysaccharide degradation - Heng,Sobroney; Sutheeworapong,Sawannee; Champreda,Verawat; Uke,Ayaka; Kosugi,Akihiko; Pason,Patthra; Waeonukul,Rattiya; Ceballos,Ruben Michael; Ratanakhanokchai,Khanok; Tachaapaikoon,Chakrit (PeerJ, 2022)
Background Cellulolytic, hemicellulolytic, and amylolytic (CHA) enzyme-producing halophiles are understudied. The recently defined taxon Iocasia fonsfrigidae consists of one well-described anaerobic bacterial strain: NS-1T. Prior to characterization of strain NS-1T, an isolate designated Halocella sp. SP3-1 was isolated and its genome was published. Based on physiological and genetic comparisons, it was suggested that Halocella sp. SP3-1 may be another isolate of I. fronsfrigidae. Despite being geographic variants of the same species, data indicate that strain SP3-1 exhibits genetic, genomic, and physiological characteristics that distinguish it from strain NS-1T. In this study, we examine the halophilic and alkaliphilic nature of strain SP3-1 and the genetic substrates underlying phenotypic differences between strains SP3-1 and NS-1T with focus on sugar metabolism and CHA enzyme expression. Methods Standard methods in anaerobic cell culture were used to grow strains SP3-1 as well as other comparator species. Morphological characterization was done via electron microscopy and Schaeffer-Fulton staining. Data for sequence comparisons (e.g., 16S rRNA) were retrieved via BLAST and EzBioCloud. Alignments and phylogenetic trees were generated via CLUTAL_X and neighbor joining functions in MEGA (version 11). Genomes were assembled/annotated via the Prokka annotation pipeline. Clusters of Orthologous Groups (COGs) were defined by eegNOG 4.5. DNA-DNA hybridization calculations were performed by the ANI Calculator web service. Results Cells of strain SP3-1 are rods. SP3-1 cells grow at NaCl concentrations of 5-30% (w/v). Optimal growth occurs at 37 °C, pH 8.0, and 20% NaCl (w/v). Although phylogenetic analysis based on 16S rRNA gene indicates that strain SP3-1 belongs to the genus Iocasia with 99.58% average nucleotide sequence identity to Iocasia fonsfrigida NS-1T, strain SP3-1 is uniquely an extreme haloalkaliphile. Moreover, strain SP3-1 ferments D-glucose to acetate, butyrate, carbon dioxide, hydrogen, ethanol, and butanol and will grow on L-arabinose, D-fructose, D-galactose, D-glucose, D-mannose, D-raffinose, D-xylose, cellobiose, lactose, maltose, sucrose, starch, xylan and phosphoric acid swollen cellulose (PASC). D-rhamnose, alginate, and lignin do not serve as suitable culture substrates for strain SP3-1. Thus, the carbon utilization profile of strain SP3-1 differs from that of I. fronsfrigidae strain NS-1T. Differences between these two strains are also noted in their lipid composition. Genomic data reveal key differences between the genetic profiles of strain SP3-1 and NS-1T that likely account for differences in morphology, sugar metabolism, and CHA-enzyme potential. Important to this study, I. fonsfrigidae SP3-1 produces and extracellularly secretes CHA enzymes at different levels and composition than type strain NS-1T. The high salt tolerance and pH range of SP3-1 makes it an ideal candidate for salt and pH tolerant enzyme discovery.
Keywords: Halophilic alkaliphilic anaerobic bacterium; Cellulolytic enzyme; Hemicellulolytic enzyme; Amylolytic enzyme; Carbohydrate-binding module; Iocasia fonsfrigidae